AB1007 Recurrent Infection after Biologicals in Autoimmune Disease: Preliminary Results with Mucosal Vaccines Recurrent Infection after Biologicals in Autoimmune Disease: Preliminary Results with Mucosal Vaccines. (15th July 2016) - Ochoa-Grullon, J.; Morado, C.; Macarron, P.; Freites, D.; Diaz, I.; Nuñez-Beltrán, M.; Rodriguez de la Peña, A.; Comins-Boo, A.; Llano Hernández, K.; Rodriguez, E.; Toledano, E.; Fernandez, B.; et al.
Abstract : Background: Over a decade has passed since the introduction of biologic therapies for autoimmune diseases. The use of biologic therapies as an adjuvant to disease-modifying anti-rheumatic drugs (DMARDs) for the treatment of systemic autoimmune diseases is rapidly expanding, due the efficacy and safety profiles of these drugs, and the better understanding of the targets of altered immune regulation. However, infections complications after biologicals are major concerns in their use. Objectives: The aim of this study is to evaluate the clinical benefit of new personalized polybacterial sublingual vaccines in patients with systemic autoimmune disease and recurrent infections. Methods: An observational study in a cohort of patients with systemic autoimmune disease and recurrent respiratory tract infections (RRTI) (3 or more episodes of upper respiratory tract infection or at least 1 pneumonia episode per year) and recurrent urinary tract infections (RUTI) (3 or more UTIs per year) was carried out. All patients underwent immunization with sublingual polyvalent preparation (Bactek®, ImmunoteK S.L. Madrid, Spain) for RRTI ( Staphylococcus spp., S. pneumoniae, K. pneumoniae, B. catarrhalis, H. influenzae ) and RUTI ( K. pneumonia, E. coli, E. faecalis, P. vulgaris ). Immunological evaluation was performed at baseline and at 6- and 12-mo., including serum immunoglobulins, IgG subclasses, specific antibodies production and B and T cell subsets counts. Results: Twenty-three patients (mean age, 55.52±15.69, 21 women and 2 men) were studied: rheumatoid arthritis (RA) (n=11, 47%), SLE (n=5, 22%), MCTD (n=3, 13%), psoriatic arthritis (n=1, 4.%), SLE/RA (n=1, 4%), DLE/Sjögren (n=1, 4%), cryoglobulinemia II (n=1, 4%) and Sjögren syndrome (n=1, 4%). All patients presented a decrease in RRTI and RUTI frequency at 6-mo of vaccine: RRTI decreased from 4.81±2.04 to 0.75±1.29 and RUTI from 4.56±1.59 to 0.22±0.44. An episode of pneumonia in two patients. Nine out of 23 patients (39%) showed alterations of the humoral immune response at baseline: hypogammaglobulinemia (n=6, 26%) and IgG2 subclass deficiency (n=3, 13%). Eleven of 23 (47%) disclosed a defect on specific antibody production to polysaccharide and protein stimuli, 7 (30%) with normal Ig serum levels and 5 (21%) with hypogammaglobulinemia. At baseline, 21 were on DMARDs (metotrexate in 12, 52%). The most used biologicals were anti-TNF-α monoclonal antibodies (n=9, 39%) followed by anti-CD20 (n=8, 34%) and tocilizumab (n=4, 17%). Conclusions: Vaccination in immunosuppressed patients with systemic autoimmune disease and recurrent infections is a commonly missed opportunity. There is an urgent need to develop alternative strategies to prevent the overuse of antibiotics in what is called the post-antibiotic era. Our preliminary results seem to be promising in these patients, reducing the infections rates, avoiding chronic use of antibiotics and subsequent resistance and adverse effects. Disclosure of Interest: None declared